Cognitive factors in elite handball: Do players` positions determine their cognitive processes? - Blecharz, J.; Wrzesniewski, K.; Siekanska, M.; Ambrozy, T.; Spieszny, M. (Journal of Human Kinetics, 2022)
For an athlete to be successful at the professional level, he or she should be characterized by extraordinary preparation in four areas: physical, technical, cognitive (related to game strategy, perception, and decision-making), and emotional (coping, emotional control). This study aimed to determine the level of selected cognitive traits in handball players while considering their sports level and assigned position on the court. Fifty handball players participated in the study. Participants consisted of 35 national team players, six first-division players, and nine second-division players. There were no significant differences between players from the elite (national team) and the sub-elite (I and II divisions) group. The results identified major differences in selective attention and short-term memory between handball players assigned to different positions (goalkeepers, compared to players in other positions, had lower attention and short-term memory). Thus, it is possible to develop a more effective psychological training program. However, it must be remembered that the results showed great variability among handball players. With this in mind, individual differences should be taken into account when planning psychological interventions.